Iklan Layanan Masyarakat Bijak Menyikapi Informasi Pada Video Pendek Untuk Orang Tua Usia 45 Tahun Ke Atas - Muhammad Ihsan Raihan; Abi Senoprabowo (Besaung : Jurnal Seni Desain dan Budaya, 2026)
The rapid growth of short-form videos on social media platforms such as TikTok, Instagram Reels, Facebook Reels, and YouTube Shorts has transformed the way people access and share information. However, this convenience has also increased the risk of misinformation and hoax dissemination, particularly among adults aged 45 years and above who often face challenges in evaluating and verifying digital information. This study aims to design a Public Service Advertisement (PSA) entitled “Check Before Sharing Short Videos” as a digital literacy education medium for adults aged 45 years and above. The research employed a qualitative approach using Robin Landa’s Visual Communication Design method, consisting of orientation, analysis, concepts, design, and implementation stages. Data were collected through questionnaires, in-depth interviews, literature reviews, and Robert N. Entman’s framing analysis. The findings indicate that 71.3% of respondents watch short videos daily, 45% trust information because of persuasive narratives, and 38.8% are influenced by content that appears to originate from official sources. Although 62.5% of respondents recognize that not all online information is accurate, verification practices remain inconsistent, increasing the potential spread of misinformation. Based on these findings, three key campaign messages were developed: checking account credibility, examining content and context, and comparing information with official sources. The campaign was implemented through posters, billboards, Facebook Ads, Instagram Ads, WhatsApp Status, and supporting media. The study concludes that a simple, communicative, and audience-oriented visual communication strategy can enhance digital literacy and encourage more critical information-sharing behavior among older adults. as an educational tool to encourage more cautious behavior before sharing short videos